The Effectiveness of Problem-Based Learning-Based E-MFI to Spur the Solving Ability of PGSD UAD Students - Puteri, Annisa; Suparman, Suparman (Jurnal Multidisiplin Indonesia, 2025)
Problem-solving skills are an important component of higher-order thinking, which is essential for students to handle a variety of problems. It includes reasoning and applying mathematical concepts to solve problems in other areas. To train students' problem-solving skills, activities that provide opportunities to practice mathematical problem-solving skills by providing opportunities to use thinking skills to develop and find problem solutions. One effective option is to apply appropriate learning approaches, such as Problem Based Learning (PBL). A lecturer is expected to have the ability to create teaching materials based on goals and needs. Currently, Electronic-Student Worksheets (e-LKM) is one of the educational programs where it can be used for evaluation of learning through information and communication technology. The purpose of this study is to determine the effectiveness of the use of PBL-based e-LKM to improve students' problem-solving skills. This type of research is an experimental research with a pretest posttest control group design. The population in this study is 2nd semester students of PGSD UAD, while the sample is class D. The data collection technique uses interviews, observations, and pretest and posttest questions for student problem solving on SPLDV material. The results of this study show that the use of PBL-based e-LKM is proven to be effective in improving students' problem-solving skills with SPLDV materials. Therefore, this study concludes that the use of PBL-based e-LKM is effective in improving students' problem-solving skills.